1998
DOI: 10.1097/00004872-199816010-00015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combination therapy with an angiotensin converting enzyme inhibitor and thiazide diuretic on insulin action in essential hypertension

Abstract: Combination therapy increased glucose production (compared with captopril alone), indicating hepatic insulin resistance. It cannot be assumed that combined preparations with angiotensin converting enzyme inhibitors will ameliorate adverse effects of high doses of thiazide diuretics on insulin action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…24,31 Our data clearly showed that the administration of ACE inhibitor did not ameliorate the adverse effects of diuretics in agreement with recently published data, which reported that combination therapy evoked hepatic insulin resistance when 5 mg of bendrofluazide was used. 26 Consequently, great care needs to be exercised in the use of these combinations notwithstanding that they are particularly efficacious in lowering BP, as it is also illustrated in the present study. It should be mentioned that it is not certain what the effects of ACE inhibitors combined with lower doses of hydrochlorothiazide will be.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…24,31 Our data clearly showed that the administration of ACE inhibitor did not ameliorate the adverse effects of diuretics in agreement with recently published data, which reported that combination therapy evoked hepatic insulin resistance when 5 mg of bendrofluazide was used. 26 Consequently, great care needs to be exercised in the use of these combinations notwithstanding that they are particularly efficacious in lowering BP, as it is also illustrated in the present study. It should be mentioned that it is not certain what the effects of ACE inhibitors combined with lower doses of hydrochlorothiazide will be.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, the putative beneficial effect of ACE inhibitors on carbohydrate metabolism remains controversial. [26][27][28][29] It is possible that the impact on sensitivity to insulin varies with different ACE inhibitors, 30 and it is dependent on the degree of underlying insulin resistance. If subjects are not particularly insulin resistant, as was the case in our patients, then it may be more difficult to reveal a beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although few studies have directly examined changes to the insulin receptor, it appears that some antihypertensive agents may modify its activity. Hypokalemia has been linked to reduced insulin-receptor sensitivity (24), but this theory has not been consistently supported (25,26). Various antihypertensive agents could alter glucose transport proteins (GLUT 1 and GLUT 4), tyrosine kinase activity, or insulin receptor binding affinity.…”
Section: Antihypertenseurs Et Glycémie : Théories Et Répercussionsmentioning
confidence: 99%
“…It has been suggested that thiazide diuretics promote hepatic insulin resistance, resulting in continued hepatic glucose production despite rising serum glucose or insulin levels (24,28). Although this effect has been observed with high-dose thiazide diuretics, it is less apparent with lower doses (12.5 mg to 25 mg of hydrochlorothiazide daily) used in current practice (28).…”
Section: Antihypertenseurs Et Glycémie : Théories Et Répercussionsmentioning
confidence: 99%